PELAKSANAAN SISTEM PELAYANAN TERPADU SATU PINTU (PTSP) DI BIDANG PENANAMAN MODAL PADA BKPM PROVINSI DAERAH ISTIMEWA YOGYAKARTA - , Endang Rarasati, SH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research are to know whether in the process of the acquisition of farm land belonging to PAG in Glagah, Kulon Progo ragency has been in accordance with the provisions of regulation number 2, 2012 conserning land acquisition for the development of the public interests, to know efforts and the implementation of object sector land acquisition during the development of tourism in the Galagah coast, Kulon Progo regency. This research used empirical legal approach meaning this research was carried out trouhg the study of the field, research to look for and determine the sociological of legal to meet the community. Interest taken by means of setting up questions were answered in writing and orally. Sample was choised by using non probability sampling technique, the sample did not have teh same to become the member. Responden was taken from the community that used the PAG land in Glagah, Kulon Progo Ragency. The informen are the regional giverment and the investor as the parties who acquisition the land for the depelovment of tourism sector in Glagah the Kulon Progo regency. The results showed that in the implementation of the development of the tourism sector that used farm land belonging to PAG in Glagah the Kulon Progo regency has been in accordance with the article 7 of regulations number 2, 2012 that in the interest of the bublic interest, acquisition the natonal development plan/the area, the strategic plan, and the work program of each agency. The acquisition of PAG land process has come to the realisation stage of the development. People who are not have the land rights certificate are not get compensation. The only get compensation related to agricultural infra structures which have been develoved by the community.